Meta-analysis of mesenchymal stem cell therapy for intrauterine adhesions: a comprehensive consideration of efficacy and safety - Gao, Jiawei; Zhou, Xinyue; Jiang, Nan; Zhang, Yongjuan; Han, Jianpeng; Jia, Tianyu; Jiang, Yanbiao; Ma, Xiaoling; Shen, Haofei (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundIntrauterine adhesions (IUA), a common gynecological condition, often result from endometrial injury and fibrosis. Traditional therapies like hysteroscopic adhesiolysis and hormone therapy show limited efficacy in endometrial repair and high recurrence rates. Stem cell therapy, particularly using mesenchymal stem cells (MSCs), has emerged as a promising alternative. This meta-analysis evaluates the efficacy and safety of MSCs therapy for IUA.MethodsWe systematically searched Embase, MEDLINE, and the Cochrane Library up to January 2025. Using random or fixed-effects models, we analyzed outcomes including pregnancy rates, endometrial thickness, menstrual improvement, and safety indicators. Subgroup analyses were performed based on stem cell sources and transplantation methods.ResultsTwelve studies with 233 patients were included. Stem cell therapy significantly improved menstrual outcomes (RR = 34.54, 95%CI: [15.07–79.18]), pregnancy rates (RR = 21.86, 95%CI: [8.60–55.56]), live birth rates (RR = 18.00, 95%CI: [6.67–48.55]), and endometrial thickness (MD = 2.28mm, 95%CI: [1.60–2.96]). Subgroup analyses indicated that adipose-derived (MD = 3.34 mm) and menstrual blood-derived (MD = 3.62 mm) stem cells exhibited the highest efficacy. Safety data indicated mild abdominal pain in 5.15% and abnormal blood indices in 4.29% of patients, with no severe complications.ConclusionStem cell therapy may improve the reproductive prognosis of patients with IUA. Autologous adipose or menstrual blood-derived stem cells via local injection are cautiously recommended. Further large-scale RCTs are needed to confirm long-term safety and optimal treatment protocols.Trial registrationThe review protocol is registered on PROSPERO with registration number CRD42025643871, and no modifications were made to the information provided at registration.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420256438.